2022
DOI: 10.1007/s10803-022-05768-9
|View full text |Cite
|
Sign up to set email alerts
|

Social-Emotional and Behavioural Difficulties in Children with Neurodevelopmental Disorders: Emotion Perception in Daily Life and in a Formal Assessment Context

Abstract: Children with neurodevelopmental disorders often have social-emotional and behavioural difficulties. The present study explored these difficulties in children (n = 50, aged 6–10 years) with autism spectrum disorder, attention-deficit/hyperactivity disorder and developmental language disorder. Parents, teachers and therapists evaluated children’s social-emotional and behavioural difficulties through a self-devised questionnaire and the Strengths and Difficulties Questionnaire. Additionally, the children, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…children with developmental disabilities, display more behavioural problems compared to their typically developing peers [ 9 ]. Nonetheless, these problems significantly affect the children’s’ daily lives and development in addition to their developmental disabilities per se [ 6 ]. Previous research has proposed that approximately 30–50% of children using similar services as habilitation services also suffer from emotional and behavioural problems, and are thus likely to have mental health treatment needs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…children with developmental disabilities, display more behavioural problems compared to their typically developing peers [ 9 ]. Nonetheless, these problems significantly affect the children’s’ daily lives and development in addition to their developmental disabilities per se [ 6 ]. Previous research has proposed that approximately 30–50% of children using similar services as habilitation services also suffer from emotional and behavioural problems, and are thus likely to have mental health treatment needs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These problems are directed outward and can negatively affect others in the child’s environment. Emotional and behavioural problems are highly prevalent in children with autism spectrum disorder, attention-deficit hyperactivity disorder, intellectual disabilities, and developmental language disorder, significantly affecting their daily lives and development [ 6 ]. The phenotypic overlap between autism and emotional and behavioural problems suggests that it is important to assess both types of problems for more accurate diagnoses and interventions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the authors investigated challenges faced by 50 children (aged 6 to 10 years old) diagnosed with ASD, ADHD, and DLD. In the research of Löytömäki et al, (2022), caregivers and experts observed that children with neurodevelopmental disorders faced various challenges in their social-emotional and behavioral domains, impacting their everyday functioning. Additionally, these children exhibited slower development in recognizing and understanding emotions compared to their typically developing peers.…”
Section: Related Workmentioning
confidence: 99%
“…Children with DDs (CwDDs) are at a signi cantly higher risk of experiencing behavioral and emotional problems than those without DDs (Totsika, 2022; Woodman et al, 2015). They experience functional di culties related to their disabilities and psychosocial challenges, including struggles with social emotion and behavior (Loytomaki et al, 2023). The challenges are associated with behavior problems, including tantrums, aggression, self-injury, and irritability (Reyes-Martin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%